The nature and properties of soils - Brady, Nyle C. (Prentice Hall, 2002)
Now in its thirteenth edition, The Nature and Property of Soils is designed to make the study of soils a fascinating and intellectually satisfying undertaking. This, the most widely-used soils textbook in the world, sets world-class standards for soils education. New photographs, diagrams and special ÒboxesÓ make the text much more engaging for readers. The text has an ecological approach that explains the fundamental principles of soil science in a manner that is relevant to students in many fields of study.